Optimalisasi Kemampuan Membaca, Menulis, dan Berhitung (Calistung) Anak sebagai Fondasi Pendidikan Dasar di RPTRA Beringin Indah - Aulia Khairunnisa; Ralfa Izaky; Raffialto Hazza Fandiar; Mona Syaira Neisa; Muhammad Daffa Arsandy (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2026)
Reading, writing, and arithmetic skills are fundamental competencies that support children's academic development. However, some children still require additional assistance to strengthen these basic abilities. This community service program aimed to improve children's literacy and numeracy skills while fostering their learning motivation through interactive and enjoyable learning activities. The program was conducted at RPTRA Beringin Indah, Rawamangun, East Jakarta, involving 15 children aged 4-7 years. The methods employed included learning assistance, interactive teaching, practical exercises, educational games, and ice-breaking activities. The results indicated high participant enthusiasm and improvement in basic reading, writing, and arithmetic skills according to each participant's level of ability. Furthermore, the program enhanced children's confidence in participating in learning activities. This program demonstrates that enjoyable and interactive learning approaches can positively contribute to the development of children's literacy and numeracy skills.